2019
DOI: 10.18671/scifor.v47n122.08
|View full text |Cite
|
Sign up to set email alerts
|

Litterfall, litter layer and leaf decomposition in Eucalyptus stands on Cerrado soils

Abstract: The success of Eucalypt cultivation in Brazil was the result of decades of research, improvement of cultivation technologies, along with favorable edaphoclimatic properties. Nowadays, Eucalypt plantations are the main source of wood in the country. However, there are persisting doubts about the impacts on hydric, chemical and biological patters on the soil by this monoculture forest. For this reason, the understanding of the nutrient biogeochemical cycle linked to the litter dynamics contributes to elucidate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
2
0
2
Order By: Relevance
“…A recent study further demonstrated that litter decomposition rates increase with RP age, potentially leading to an improvement of soil quality in older plantations [32]. In contrast, soil nutrients levels decline dramatically after the establishment of Eucalypt plantations, which has been proposed to be related to their poor-quality and highly recalcitrant litterfall [50,51]. In congruence with these previous results, we found greater soil C, N and P content in RP than in EP ( Figure S2).…”
Section: Microbial α-Diversity and Structure And Relationships To Soisupporting
confidence: 90%
“…A recent study further demonstrated that litter decomposition rates increase with RP age, potentially leading to an improvement of soil quality in older plantations [32]. In contrast, soil nutrients levels decline dramatically after the establishment of Eucalypt plantations, which has been proposed to be related to their poor-quality and highly recalcitrant litterfall [50,51]. In congruence with these previous results, we found greater soil C, N and P content in RP than in EP ( Figure S2).…”
Section: Microbial α-Diversity and Structure And Relationships To Soisupporting
confidence: 90%
“…The permanence time of organic eucalypt residue is long, and can take five years [60]. Lignin, cellulose, waxes, and tannins, such as leaves, branches, and petioles, still remain, reducing the rate of decomposition [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the low fertility, high concentrations of exchangeable aluminum, and high acidity rates in the biome [ 52 , 53 ], eucalyptus stands have been able to expand due to the adaptability of this exotic species to the edaphoclimatic conditions in the Cerrado domain [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%